Cultural Precarity: Migrants' Positionalities in the Light of Current Anti-immigrant Populism in Europe. (3rd September 2018) - Nowicka, Magdalena
ABSTRACT: The Brexit referendum was an earthquake to those in otherwise privileged positions: white intra-European migrants. Poles form the largest among these groups in the UK. As much as they are vulnerable to discrimination as non-British citizens, these migrants benefit from their whiteness and European heritage. They are objects of anti-immigrant campaigns, but they are not free of anti-immigrant sentiments and racist attitudes. This article uses the notion of 'cultural precarity' to highlight their ambivalent positionalities in Britain and how those have been changing since the Brexit vote. Drawing on three studies conducted among Poles in England between 2010 and 2017, it explores how the neoliberal and culturalist logics of belonging determine the migrants' conditions. By applying the lens of 'cultural precarity', the article is attentive to both to the migrants' vulnerability and the moments of everyday resistance to anti-immigrant populism now at work across Europe. The Brexit case is instructive for other contexts for it demonstrates how migrants construct their own cultural and racial proximity to dominant groups to counter vulnerability and secure inclusion.